Prosper and Pipesim software for modeling of wells equipped with ESP systems - Sredojević Aleksandar; Martinović Bojan; Repac Milan D.; Jovanović-Sovtić Dino; Ponoćko Ana; Crnogorac Miroslav; Danilović Dušan (Podzemni Radovi, 2025)
When the pressure at the bottom of the well is insufficient to overcome the total pressure losses from the bottom of the well to the separator, production using reservoir energy is no longer possible, and the well ceases to naturally flow. To enable fluid production from the well again, it is necessary to apply some artificial lift systems. The most applicable artificial lift methods are gas lift (GL), sucker rod pumps (SRP), electric submersible pumps (ESP), progressive cavity pumps (PCP), and hydraulic pumps (HP). This paper will delve into the modeling of wells equipped with electric submersible pump (ESP) systems, which are a widely adopted artificial lift methods in the oil and gas industry. This research aims to create accurate models that reflect the performance of these systems. For the modeling we will use industry standard software Prosper and Pipesim and perform a comparative study between both. Study will aim to show advantages and disadvantages of using both software, contributing to the understanding of their applicability in optimizing ESP system performance. Ultimately, this work seeks to enhance the knowledge base regarding effective exploitation methods in hydrocarbon extraction. We begin by explaining the cessation of the well's natural flow, followed by a transition to an artificial lift method. The second section focuses on the methodology, explaining how each software Pipesim and Prosper employs specific empirical formulas and correlations for modeling, and how they use NODAL analysis to predict the well's behavior. The final part of the paper presents an actual case study in which the output data from both software programs are compared with the actual field-collected data from the ESP-equipped Well-X-1. Additionally, this analysis offers valuable insights into the strengths and limitations of using both Prosper and Pipesim, contributing to a deeper understanding of their applicability in optimizing ESP system performance. Ultimately, this study aims to enhance the knowledge base on effective exploitation methods in hydrocarbon extraction.